1999
DOI: 10.4269/ajtmh.1999.60.806
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of California and Bunyamwera serogroup (Bunyaviridae) virus infections in native populations of Alaska.

Abstract: Abstract. This study investigated the geographic distribution and prevalence of antibodies to California and Bunyamwera serogroup viruses in Native populations of Alaska, and demographic and ecologic risk factors associated with exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 28 publications
(63 reference statements)
4
30
0
Order By: Relevance
“…3,34,[37][38][39][40][41] The geographic distribution of our cases was similar, mostly in the northern contiguous United States, but some of our case patients resided in areas where human JCV infections have not previously been documented (e.g., Idaho, Massachusetts, Mississippi, New Hampshire, Oregon, Pennsylvania, and Rhode Island). Wisconsin reported the most cases during our study period.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…3,34,[37][38][39][40][41] The geographic distribution of our cases was similar, mostly in the northern contiguous United States, but some of our case patients resided in areas where human JCV infections have not previously been documented (e.g., Idaho, Massachusetts, Mississippi, New Hampshire, Oregon, Pennsylvania, and Rhode Island). Wisconsin reported the most cases during our study period.…”
Section: Discussionmentioning
confidence: 53%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19] JCV neutralizing antibodies have been found in various mammals throughout mainland North America, 13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and identified in humans throughout the United States. [1][2][3][4][5]34,[37][38][39][40][41] JCV is a member of the California serogroup viruses, which include La Crosse virus (LACV), California encephalitis virus, and snowshoe hare virus. 42 Although the presence of anti-JCV immunoglobulin (Ig) M detected by enzyme-linked immunosorbent assay (ELISA) is usually evidence of a recent JCV infection, it also may indicate infection with another closely related California serogroup virus.…”
mentioning
confidence: 99%
“…A number of serologic investigations have determined the seroprevalence of CVV in various vertebrates but these studies have mostly been confined to the United States. [21][22][23]37,[46][47][48][49][50][51] For instance, 19% of sheep sampled in Texas in 1981 were seropositive for CVV. 46 In another study, antibodies that neutralized CVV were detected in 84 (95%) of 88 horses, 61 (52%) of 118 cattle, and 6 (27%) of 22 Neutralizing antibodies to CVV were also detected in 100 (72%) of 138 white-tailed deer in Minnesota in 1988 and 1989.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were previously demonstrated during Bunyamwera serogroup virus infection surveys in Alaska. 9,21,22 A previous study noted the presence of TS virus in states around the Gulf coast and LK virus in western Texas, Colorado, Utah, and southern California. 9,24 Although antibodies to TS virus and LK virus were observed in sera from many states, test results for non-cross-reacting antibodies in this study indicated the presence of monospecific antibodies to TS virus in four of 19 states and to LK virus in all northeastern and north central states except Connecticut, Kentucky, Maryland, Maine, Minnesota, Vermont, and Alaska and Hawaii, indicating the presence of these viruses in many more states than thought earlier.…”
Section: Discussionmentioning
confidence: 99%
“…4,9,[16][17][18] Bunyamwera serogroup viruses are known to cause undifferentiated illness, and rarely, central nervous system disease in humans in Africa, Brazil, and Argentina. 19,20 Antibodies to CV virus, 4,9,17,18 Northway (NW) virus, 4,[21][22][23] and Teneswa (TS) virus 24 were reported in humans in the United States and Canada. In California, evaluation of 702 individuals for antibodies to selected bunyavirus showed 6.4% had antibodies to California serogroup viruses and 0.3% to Bunyamwera serogroup viruses.…”
Section: Introductionmentioning
confidence: 99%